Using PF-MOUTH GELTM for Sore or Painful Tongue Improved Symptoms and Stabilized Dryness and Trapping of Food: A Case Report - Shuichi Tsubura; Masahide Kanazawa; Shunya Oka; Rika Hirama; Tsutomu Tsubura (Dentistry, 2021)
We describe herein the case of a 72-year-old woman with persistent and symptomatic sore or painful tongue (SPT) treated using PF-MOUTH GELTM (PF-Gel; Daiichi-Sangyo, Osaka, Japan), which includes 30% fucoidan and 0.75% sword bean. PF-MOUTH GELTM was applied to the tongue and kept in place for 3-min. Application was performed twice a day (morning and evening) for 3-months, and resulted in marked improvement of symptomatic sore or painful tongue. Because only one case was reported in this study, clinical trials are required to confirm the efficacy and safety of topical PF-MOUTH GELTM for the treatment of symptomatic sore or painful tongue.